The Meaning of an Offering. The Role of Sacrifice in Jan Patočka's Thought - Walicki, Jakub (Hybris, 2019)
In the paper I try to reconstruct and investigate the reasons which inclined Patočka to strongly expose the problem of sacrifice in his philosophical thought. To do so, I highlight the relationship between sacrifice, the meaning of life and three platonic ideas of goodness, beauty and truth, assuming sacrifice to be a perfect instrument of incorporating them. Finally, I argue that the nature of sacrifice is inherently equivocal and all studies concerning it should include its negative aspects.